2017
DOI: 10.1002/nop2.87
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers’ attributes to promote change in their wards: a qualitative study

Abstract: AimThe aim of this study was to explore the processes that nurse managers use to promote change in their wards.DesignQualitative research.MethodsA grounded theory approach was used. Participants were 23 nurse managers and 17 nurses in Japan. Interviews were conducted between March 2014 – December 2015. Mainly, nurse managers’ data was analysed.ResultsThe change process led by the nurse managers was depicted as a four‐phased process of “having beliefs and empathizing with staff nurses to achieve goals explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 15 publications
(28 reference statements)
2
34
0
1
Order By: Relevance
“…The mean POPAC scores over a sample of nurses can be utilized to measure the quality of care for people with dementia in hospitals. Nursing professionals and nursing managers can use the outcomes as indicators to determine which areas of care can be improved in their ward (41). Additionally, the POPAC can be used in the education of nurses and nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…The mean POPAC scores over a sample of nurses can be utilized to measure the quality of care for people with dementia in hospitals. Nursing professionals and nursing managers can use the outcomes as indicators to determine which areas of care can be improved in their ward (41). Additionally, the POPAC can be used in the education of nurses and nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…That insight empirically supports the notion that work arrangements can reflect work motivations, which may influence whom and how nurse managers mentor (Gan, ). Nurse managers invest much of their time and resources in mentoring nurses (Kodama & Fukahori, ; Sveinsdóttir, Ragnarsdóttir, & Blöndal, ). Mentoring helps to disseminate knowledge and to promote evidence‐based practice (Abdullah et al, ; Karlberg Traav, Forsman, Eriksson, & Cronqvist, ) as well as to impart career insights and to foster supportive relationships (Simpson & Simpson, ).…”
Section: Discussionmentioning
confidence: 99%
“…This includes the idea of indirect patient care being aside the actual care work (Ausserhofer et al., ; Ball et al., ; Menon, ). Furthermore, because previous studies have shown that nurses perceive physical demands as one of the main challenges in their work (Erkkilä et al., ; Kodama & Fukahori, ; Trydegård, ), our second hypothesis was that the respondents are more approving towards robots that assist in physically burdening care tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Telepresence offers an important and interesting prospect of reorganizing and prioritizing tasks in care work. At the moment, nursing staff is concerned about resource shortages as well as administrative tasks and travelling taking time from actual care work (Ausserhofer et al, 2014;Ball, Murrells, Rafferty, Morrow, & Griffiths, 2014;Kodama & Fukahori, 2017;Menon, 2015;Trydegård, 2012).…”
Section: Introductionmentioning
confidence: 99%